Tourism Suitability Index and Ecological Carrying Capacity in the Citepus, Karang Hawu, and Cikaso Beaches, Sukabumi Regency, Indonesia - Annida, Shafira Bilqis; Baihaqi, Faqih; Rahmawati, Riyanti; Wahyuningtias, Yusfi Sri (Department of Forest Resources Conservation and Ecotourism - IPB University, 2026)
Indonesia is known as a country with the second-longest coastline in the world. This geological condition offers promising potential for coastal tourism. However, the potential of coastal tourism is not without its management challenges. This study was conducted to analyze the tourism suitability index and ecological carrying capacity of coastal tourism at Citepus, Karang Hawu, and Cikaso Beaches. The assessment was conducted for three tourism categories: beach recreation, swimming, and camping. The tourism suitability index was assessed based on 12 physical beach criteria, including beach type and width, substrate type, depth, water transparency, current velocity, wave height, beach slope, vegetation, the presence of dangerous biota, freshwater availability, and scenery diversity. The ecological carrying capacity of the tourism area was calculated based on the coastal area and the optimal ecotourism area criteria for each type of recreation. The study was conducted from April to June 2025. The results of the tourism suitability index assessment showed that Citepus and Cikaso Beaches were categorized as very suitable for all three tourism activities. In contrast, Karang Hawu Beach was categorized as very suitable for beach recreation, moderately suitable for swimming, and conditionally suitable for camping. The coastal ecological carrying capacity assessment varied by beach size. Citepus Beach can accommodate 503 tourists for beach recreation, 378 for swimming, and 1,558 for camping. Karang Hawu Beach can accommodate 403 tourists for recreation, 302 for swimming, and 1,171 for camping. Cikaso Beach can accommodate 269 tourists for beach recreation, 201 for swimming, and 957 for camping.